“The Volunteered Geographic Information in Land Administration: Crowdsourcing Techniques in Cadastral Surveys”. - Μπασιούκα, Σοφία (Σχολή Αγρονόμων και Τοπογράφων Μηχανικών, 2015)
This research poses the principal question of whether the spatial and attribute data collected by volunteer landowners could be used in official Land Administration Systems (LAS) by mainly exploring the potential introduction of crowdsourcing techniques into official cadastral surveys as a simplified and transparent procedure undertaken with the aid of citizens. This research aims to propose an alternative model based on Volunteered Geographic Information (VGI) that may be applied in various crowdsourced projects worldwide and explores its viability through theoretical investigation and practical experiments carried out by testing various methodologies and recruiting volunteers in various areas of interest. The Hellenic Cadastre (HC) project was selected as an interesting project of great national importance that may be used as a forerunner for this research. The research aims to introduce a new and open crowdsourced process, simplified and faster than previous models, where costs will be reduced and citizens will be actively involved. This thesis presents the possibilities and perspectives of the potential use of crowdsourcing techniques for spatial and attribute data manipulation for interim cadastral maps and it is divided into two main stages: literature review and practical documentation. The study focuses on the use of new technologies, web-mapping tools, free-of-charge applications supported by smartphones, the first crowdsourced map, (OpenStreetMap (OSM)) and follows the sociological trend to be more citizen centered in decision making policies. Generally, this research follows the trend adopted during the last decade by governmental bodies towards open, inexpensive, quick and transparent processes involving citizens and applying new technologies to cadastral mapping. It is being gradually observed that the current trend for crowdsourcing will retain a fundamental role in the recent revolutionary use of spatial data. All the experiments carried out within this research, illustrate a great willingness of citizens towards participation and demonstrated new opportunities that could be adopted.